Security of Wireless Sensor Networks in Biomedical - Alshowkan, Muneer; Odeh, Ammar; Bach, Christian (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Wireless sensor networks are rapidly growing as they have many outstanding characteristics such as the low power consumption, remote location sensing, low cost wirelessly communication and mobility. There has been increase in using wireless sensor networks in the biomedical and healthcare. However, using wireless sensor network introduce new challenges that are related to privacy and security. As well as the information related to the patient besides the other parities in the healthcare facilities. For instance, the information related to the doctors, nurses and the workers. We reviewed the latest approaches that are related to wireless sensor security in the literature and identified the most affective factors in wireless sensor networks that are affecting the privacy and the security when employing these network especially in biomedical field. We discuss the tradeoff between increasing the security and the network performance. Moreover, we provide several solution to increase the security of wireless sensor network while maintaining the required performance. - In this we have covered the security issues that are related to the computing network. However, the risk from using the devices in the human body are not the scope of this paper. The purposed solutions are more effective when taking in consideration the factors the effect the wireless sensors such as the battery life or providing new a valid source of power. This paper provide the challenges of using the wireless sensor network in biomedical field and how to solve most of these issues. Solutions are provided to be implemented with the consideration of the other factors provided to make the wireless sensor network more secure.